Akkermansia muciniphila: is it the Holy Grail for ameliorating metabolic diseases?. (1st January 2021) - Yan, Juan; Sheng, Lili; Li, Houkai
ABSTRACT: The increasing prevalence of metabolic diseases has become a severe public health problem. Gut microbiota play important roles in maintaining human health by modulating the host's metabolism. Recent evidences demonstrate that Akkermansia muciniphila is effective in improving metabolic disorders and is thus considered as a promising "next-generation beneficial microbe". In addition to the live A. muciniphila, similar or even stronger beneficial effects have been observed in pasteurized A. muciniphila and its components, including the outer membrane protein Amuc_1100, A. muciniphila -derived extracellular vesicles (AmEVs), and secreted protein P9. Hence, this paper presents a systemic review of recent progress in the effects and mechanisms of A. muciniphila and its components in the treatment of metabolic diseases, including obesity, type 2 diabetes mellitus, cardiovascular disease, and nonalcoholic fatty liver disease, as well as perspectives on its future study.